C-Reactive Protein Is Elevated Only in High Creatine Kinase Responders to Muscle Damaging Exercise - Isaacs, Ashwin W.; Macaluso, Filippo; Smith, Carine; Myburgh, Kathryn H. (Frontiers in Physiology, 2019)
The purpose of this study was to investigate if exertional rhabdomyolysis induced by an acute bout of plyometric exercise in untrained individuals was associated with histological characteristics of skeletal muscle, creatine kinase (CK) polymorphism or secondary damage. Twenty-six healthy male untrained individuals completed a bout of plyometric exercise (10 sets of 10 maximal squat jumps, with each standardised to achieve at least 95% of individual maximal jump height). Blood samples were taken and perceived pain scored immediately before the exercise intervention and 6 hours, 1, 2 and 3 days post-intervention. Muscle biopsies were collected 9 or 4 days before (baseline) and 3 days after plyometric jumps. Subjects were divided into two groups, high (n=10) and low responders (n=16), based on a cut-off limit for exertional rhabdomyolysis of peak CK activity ≥1000 U/L in any post-exercise blood sample. Perceived pain was more severe assessed in squat than standing position. Low responders perceived more pain at 6 hours and 1 day, while high responders perceived more pain than low responders on days 3 and 4 after exercise; structural (dystrophin staining) and ultra-structural (transmission electron microscopy) analysis of muscle fibres revealed no baseline pathology; damage was evident in all individuals in both groups, with no difference between high and low responders in either damage or fibre type proportion. High responders had significantly higher total white blood cell and neutrophil counts 6 hours and significantly higher C-reactive protein (CRP) 6 hours and days 1 and 2 after exercise compared to low responders. High responders had significantly greater muscle myeloperoxidase (MPO) levels in baseline and 3 day post-exercise biopsies compared to baseline of low responders. MLCK C49T single polymorphism was present in 26% of volunteers, whose CK responses were not higher than those with MLCK CC or CT genotype. In conclusion, perceived pain is more effectively assessed with potentially affected muscle under eccentric strain, even if static. High CK responders also have pronounced CRP responses to unaccustomed plyometric exercise intervention. Exertional rhabdomyolysis after unaccustomed eccentric exercise may be related to underlying inability to resolve intramuscular MPO.